Pharmacokinetics of nevirapine in HIV and tuberculosis-coinfected children receiving antiretroviral fixed-dose combination tablets while receiving rifampicin-containing tuberculosis treatment and after rifampicin discontinuation - Prasitsuebsai W. (2017)
We assessed the pharmacokinetics of nevirapine in HIV and tuberculosis-coinfected children while they were receiving nevirapine-containing fixed-dose combination tablets with rifampicin-based tuberculosis treatment and after discontinuation. The median age (range) was 9.7 (4.4-11.7) years. The nevirapine area under the concentration versus time curve from 0 to12 hours and trough concentration with rifampicin were 85.3 (40.5-170.7) mg.h/mL and 6.4 (3.00-13.27) mg/mL, respectively, providing adequate exposure. © 2012 by Lippincott Williams & Wilkins.